2011
DOI: 10.1016/j.geoderma.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors of spatial distribution of soil salinity on flat irrigated terrain

Abstract: Inefficient irrigation and the excessive use of water on agricultural land in the Aral Sea Basin over several decades have led to saline soils. The main objective of this paper is to identify the environmental predictors to model the spatial distribution of soil salinity in a highly irrigated landscape. Soil salinity at farm scale was measured in the topsoil (Total Dissolved Solids, TDS) and down to a depth of 1.5 m by electromagnetic conductivity meter (CMv) over a regular grid covering an area of approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 23 publications
2
56
0
3
Order By: Relevance
“…The reason behind the tendency of the MARS models to overestimate the measured ECe is not clear, but it can probably be attributed to spectral characteristics of the imagery or model generalization [18]. In spite of this tendency, the MARS models are satisfactory and resulted in very good R 2 values for all maps, indicating that the models mostly learned well and had good generalization ability (Figure 8b,d) [73][74][75]. Therefore, the excess accumulation of salts at the soil surface is probably varied due to the distribution of different factors across the study area.…”
Section: Soil Salinity: Mapping and Assessmentmentioning
confidence: 98%
See 1 more Smart Citation
“…The reason behind the tendency of the MARS models to overestimate the measured ECe is not clear, but it can probably be attributed to spectral characteristics of the imagery or model generalization [18]. In spite of this tendency, the MARS models are satisfactory and resulted in very good R 2 values for all maps, indicating that the models mostly learned well and had good generalization ability (Figure 8b,d) [73][74][75]. Therefore, the excess accumulation of salts at the soil surface is probably varied due to the distribution of different factors across the study area.…”
Section: Soil Salinity: Mapping and Assessmentmentioning
confidence: 98%
“…Therefore, the excess accumulation of salts at the soil surface is probably varied due to the distribution of different factors across the study area. For example, Akramkhanov et al [74] found that the spatial distribution of soil salinity in the Khorezm Province, Uzbekistan, is likely due to soil texture, land management practices, and water table. We found that the spatial distribution of soil salinity was variable over the investigated areas.…”
Section: Soil Salinity: Mapping and Assessmentmentioning
confidence: 99%
“…This has caused elevated groundwater tables and enhanced capillary rise during the crop growing season. Resultant secondary soil salinization can be observed in irrigated croplands throughout the entire region [34]. Adverse impacts of soil and groundwater salinity on crop yields, as well as land abandonment due to LD are increasingly common in the study region.…”
Section: Study Areamentioning
confidence: 97%
“…The cotton and winter wheat cropping pattern is regulated by the state policy that defines cultivation areas for cotton and yield targets for both crops [36]. Land degradation in the form of secondary soil salinization is particularly widespread in these lowland areas, mainly due to inefficient irrigation and drainage practices which cause a rise in groundwater tables and threaten crop yields [37,38].…”
Section: Study Areamentioning
confidence: 99%